التفاعل الحي مع القرآن الكريم (دراسة في تحديات وإبداعات حفاظ القرآن في زمن جائحة كورونا-١٩) - Hamka Hasan (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The tradition of memorizing the Quran during the COVID-19 pandemic experienced obstacles, especially for students using Arabic as their language of instruction. This study, therefore, aims to explore the obstacles and creativity during their task of memorizing and repeating the Quran (murojaah) , particularly in answering the question; what are their challenges and creativity on learning during the COVID-19 pandemic and to what extent this creativity can be maintained in normal periods. The findings of this study prove that among their obstacles are the burdensome learning method, internet network problems, and limited pulse. While their creativity is the use of new applications, memorization with partners, and voice recording. Furthermore, this study also demonstrates that the pandemic does not restrict them to be successful in their tasks and make their memorization fluent, they, even, can encourage new creativity that can be maintained in normal times. This research method is in the theme of living Quran research which makes the tradition of memorizing as part of the type of community interaction with the Quran.